2007
DOI: 10.1155/2007/19564
|View full text |Cite
|
Sign up to set email alerts
|

Association of GST Genes Polymorphisms with Asthma in Tunisian Children

Abstract: Background. A positive association between genetic polymorphism and asthma may not be extrapolated from one ethnic group to another based on intra- and interethnic allelic and genotype frequencies differences. Objective. We assessed whether polymorphisms of GST genes (GSTM1, GSTT1, and GSTP1) are associated with asthma and atopy among Tunisian children. Methods. 112 unrelated healthy individuals and 105 asthmatic (73 atopic and 32 nonatopic) children were studied. Genotyping the polymorphisms in the GSTT1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 36 publications
9
32
1
Order By: Relevance
“…In this study, we found that the frequencies of GSTP1 exon 5 genotypes in healthy controls were similar to those in Tunisia (Hanene et al, 2007), also close to those reported in European populations (Harries et al, 1997;Ryberg et al, 1997;van Lieshout et al, 1999;Rodríguez et al, 2005), but lower than Asiatic groups (Chan-Yeung et al, 2007). The different distribution in the 105Val allele between populations may be relevant to different GSTP1-metabolizing activities and to differences in susceptibility to specific exposure-induced diseases in different races.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, we found that the frequencies of GSTP1 exon 5 genotypes in healthy controls were similar to those in Tunisia (Hanene et al, 2007), also close to those reported in European populations (Harries et al, 1997;Ryberg et al, 1997;van Lieshout et al, 1999;Rodríguez et al, 2005), but lower than Asiatic groups (Chan-Yeung et al, 2007). The different distribution in the 105Val allele between populations may be relevant to different GSTP1-metabolizing activities and to differences in susceptibility to specific exposure-induced diseases in different races.…”
Section: Discussionsupporting
confidence: 88%
“…The Val105/Val105 genotype distribution of GSTP1 in the present control group (10.43%) was similar to that in another Tunisian sample (10.7%) (Hanene et al, 2007), higher compared to Taiwanese (3%) and European-Americans (7%), but lower than in African-Americans (19%) (Watson et al, 1998). The difference in frequencies of genotype may be relevant to different enzyme-metabolizing activities and types of dominant functional enzymes against oxidative stress in different races.…”
Section: Discussionsupporting
confidence: 79%
“…When the distribution of the GSTM1 and GSTT1 null genotypes were compared between linguistic groups of the control subjects, different percentages were obtained and GSTT1 null genotypes was statistically different between the Afro-Asiatic and the Nilo-Saharan groups (P = 0.01). Difference in frequencies between Africans population is reported; Egyptians 15-29% (Abdel-Rahman, 1996;Hamdy et al, 2003), Tunisians 29% (Hanene et al, 2007) and Zimbabweans 26% (Masimirembwa, et al, 1998). generally speaking the GSTM1 frequency (10.3%) is close to sub-Saharan Africa range; Nigerians 22% (Zhao et al, 1994) and Zimbabweans 24% (Masimirembwa, et al, 1998).…”
Section: Drug Metabolizing Enzymesmentioning
confidence: 85%
“…Primer sequences and restriction enzyme 8,20,21 used in the study for different polymorphisms are given in Supplementary Table S1.…”
Section: Genotypingmentioning
confidence: 99%